Asymmetric effects of acute stress on cost and benefit learning. (April 2022) - Voulgaropoulou, Stella D.; Fauzani, Fasya; Pfirrmann, Janine; Vingerhoets, Claudia; van Amelsvoort, Thérèse; Hernaus, Dennis
Abstract: Background: Humans are continuously exposed to stressful challenges in everyday life. Such stressful events trigger a complex physiological reaction – the fight-or-flight response – that can hamper flexible decision-making and learning. Inspired by key neural and peripheral characteristics of the fight-or-flight response, here, we ask whether acute stress changes how humans learn about costs and benefits. Methods: Healthy adults were randomly exposed to an acute stress (age mean=23.48, 21/40 female) or no-stress control (age mean=23.80, 22/40 female) condition, after which they completed a reinforcement learning task in which they minimize cost (physical effort) and maximize benefits (monetary rewards). During the task pupillometry data were collected. A computational model of cost-benefit reinforcement learning was employed to investigate the effect of acute stress on cost and benefit learning and decision-making. Results: Acute stress improved learning to maximize rewards relative to minimizing physical effort (Condition-by-Trial Type interaction: F (1, 78)= 6.53, p  = 0.01, n 2 G = 0.04; reward > effort in stress condition: t (39) = 5.40, p  < 0.01). Computational modelling revealed that asymmetric learning could be explained by changes in the learning rates of reward value and action cost [condition-by-learning rate (αR, αE) interaction: F (1, 78)= 6.42, p  = 0.01, n 2 G = 0.03; αE> αR in control condition: t (39) = −4.75, p  < 0.001]. This process was associated with distinct alterations in pupil size fluctuations. Data and scripts are available (https://osf.io/ydv2q/). Conclusions: Here we demonstrate that acute stress is associated with asymmetric learning about reward value versus action cost, thereby providing new insights into learning strategies under acute stress, which, depending on the context, may be maladaptive or beneficial. Our pupillometry and physiological results tentatively link asymmetric cost and benefit learning to stress-related changes in catecholamine activity. Highlights: Acute stress prioritizes the importance of maximizing reward value over minimizing action cost. Acute stress alters choice preferences by selectively impacting the learning rate for reward value and action cost. Pupillometry and physiological results link asymmetric cost-benefit learning with changes in neuromodulatory systems.